Heha Sky View: Role Model for MSME Partner-Based Tourism in Yogyakarta - Siswanto, Agus; Hidayat, Abdul Choliq (AIBPM Publisher, 2023)
This research is a qualitative descriptive method, revealing brilliant ideas, building a tourism business strategy: partnership with Micro, Small and Medium Enterprises (MSMEs). Data collected by interviews, discussions, observations, and secondary data. Visited by 15,000 people in one day during peak season, Heha Sky View (HSV), located on the hillside of Patuk, Yogyakarta, Indonesia, offers beautiful views, sunset, very instagrammable of various selfie photo spots, the mountains and culinary delights. Street food stalls, affordable prices, provided by 25 MSME units connected by skybridge. The community around as a buffer zone is also the vision of the HSV owner. Benefits for MSMEs, communities, multiplier effect trades, and transportation. Capital of 10 billion rupiah as a ROI for 4 (four) years, MSMEs caring, empowering, and benefiting stakeholders. HSV should be a role model for the tourism business. The formulation is to make natural and artificial scenery as well as innovation tourism, quickly returns capital, and sustainable.